Rice grain yield as affected by subsoiling, compaction on sowing furrow and seed treatment - Veneraldo Pinheiro; Luís F. Stone; José A. F. Barrigossi (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to determine the effects of subsoiling, compaction on sowing furrow and seed treatments with insecticides on the grain yield of upland rice cultivated under no-tillage. Two experiments were carried out, one in an area with and the other in an area without subsoiling, in which five seed treatments combined with five compaction pressures on the sowing furrow were compared in a randomized block design, in a factorial scheme, with three replicates. The seed treatments were: T0 - without treatment, T1 - imidacloprid + thiodicarb, T2 - thiamethoxam, T3 - carbofuran, and T4 - fipronil + pyraclostrobin + thiophanate methyl. The compaction pressures were: 25, 42, 126, 268 and 366 kPa. Subsoiling positively affected rice yield in the presence of higher compaction pressures on the sowing furrow. Seed treatment was effective at increasing rice grain yield only at the lowest compaction pressures. Rice yield showed quadratic response to compaction on the sowing furrow, with maximum values obtained at pressures ranging from 238.5 to 280.3 kPa.